Development of sprayer nozzle of The unpacked saturator for dissolved air flotation process. - Adlan, Mohd. Nordin; Abdul Aziz, Hamidi (Universiti Sains Malaysia, 2008)

(untitled)
Dissolved air flotation (DAF) process becomes prominent in water treatment technology all over the world. This process had been well-accepted as an alternative for sedimentation due to its potential to remove very small or light particles in a shorter period, simplicity of the design and only required less area.